1985
DOI: 10.1073/pnas.82.10.3063
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature magnetic circular dichroism studies of native laccase: spectroscopic evidence for exogenous ligand bridging at a trinuclear copper active site.

Abstract: The detailed nature of N-binding at the multi-copper active site in native laccase is investigated through a combination of low-temperature magnetic circular dichroism (LTMCD) and absorption spectroscopies. This combination of techniques allows charge-transfer spectral features associated with N-binding to the paramagnetic type 2 Cu(II) to be differentiated from those associated with binding to the antiferromagnetically coupled, and therefore diamagnetic, binuclear type 3 Cu(II) site. Earlier absorption titrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 24 publications
6
82
0
Order By: Relevance
“…Structural descriptions of R Az have been available from both spectroscopy and crystallography. Spectroscopy first determined that the azide must bridge the T2 and T3 Cu centers in R Az (14,15). This in fact provided the first evidence for the presence of the trinuclear Cu clusters in biology, which was confirmed by the first crystal structure of an MCO, ascorbate oxidase (AO) (16).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Structural descriptions of R Az have been available from both spectroscopy and crystallography. Spectroscopy first determined that the azide must bridge the T2 and T3 Cu centers in R Az (14,15). This in fact provided the first evidence for the presence of the trinuclear Cu clusters in biology, which was confirmed by the first crystal structure of an MCO, ascorbate oxidase (AO) (16).…”
mentioning
confidence: 78%
“…4, band 6) and R Az reflect the similar T2 site geometries in the two forms. Alternatively, the N 3 Ϫ nb 3 Cu T3␣/T3␤ CT transitions at Ϸ29,400 cm Ϫ1 in the absorption and CD spectra of R Az (14) are Ϸ3,000-6,000 cm Ϫ1 higher in energy than those of NI Az , consistent with having the additional coordination of the OH Ϫ bridging ligand to the T3 Cu atoms in R Az (27).…”
mentioning
confidence: 82%
“…It is well known that the optical absorption spectra of metalloproteins depend markedly on temperature (Knowles et al 1975;San Biagio et al 1977;Dooley et al 1979;Solomon et al 1980;Browett and Stillman 1984;Allendorf et al 1985;Cordone et al 1986;Leone et al 1987;Di Iorio et al 1991;Vitrano et al 1993); as an example we shown in Fig. 1 the Sorer band of Asian elephant MbCO at various temperatures in the range 300-20 K. Three main effects are observed on lowering the temperature: i) halfwidth narrowing, ii) peak frequency shift, iii) integrated intensity variations.…”
Section: Introductionmentioning
confidence: 84%
“…There is experimental evidence in earlier studies that the type 2 copper is close to the type 3 copper and forms a trinuclear active copper site [81][82][83][84][85][86]. Solomon and associates described this metal binding site as a trinuclear active site, based on spectroscopic studies of azide binding to tree laccase [85,86]. In ascorbate oxidase, the putative binding site for the reducing substrate is the type 1 copper [43].…”
Section: Native Oxidized Enzymementioning
confidence: 98%
“…The binding of azide in laccase as well as to ascorbate oxidase has been studied extensively by Solomon and co-workers [101,[105][106][107] and by Marchesini and associates [108,109] by spectroscopic techniques. The derived spectroscopic models involve the binding of two azide molecules for laccase and three azide molecules for ascorbate oxidase with different affinities.…”
Section: Azide Form Of Ascorbote Oxidosementioning
confidence: 99%